In situ surface reduction for accessing atomically dispersed platinum on carbon sheets for acidic hydrogen evolution. Issue 44 (4th November 2021) - Quan, Weiwei; Ruan, Xinglin; Lin, Yingbin; Luo, Jiewei; Huang, Yiyin
Abstract : Atomically dispersed Pt catalysts were prepared by in situ surface reduction, resulting in efficient acidic HER with a current density of 84.3 mA cm −2 at the overpotential of only 50 mV, and better catalytic durability compared to commercial Pt/C. Abstract : Exploring the simple yet well-controlled synthesis of atomically dispersed Pt catalysts is a crucial endeavour for harvesting clean hydrogen via the kinetics-favoured acidic electrochemical water splitting technique. Here we employed the use of defective carbon sheets by KOH etching as a substrate for the in situ surface reduction of Pt(iv ) ions to prepare atomically dispersed Pt. Physical and electrochemical characterizations reveal a strong interaction between the carbon substrate and Pt species, providing the basis for the in situ surface reduction. The atomically dispersed Pt electrocatalyst exhibited high HER performance in a sulfuric acid electrolyte, with an overpotential as low as 55 mV at a current density of 100 mA cm −a, and better catalytic durability compared to the commercial Pt/C. The mechanism study revealed that the full utilization of atomically dispersed Pt and the optimized catalyst surface may enhance the recombination of adsorbed *H via the Volmer–Tafel mechanism to produce H2 at a high efficiency. In the light of high activity, durability, and low cost, the atomically dispersed Pt material is promising for acidic HER application.